The Impact of Immigration on the UK Labour Market - Christian Dustmann; Francesca Fabbri; Ian Preston (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2005)
This paper provides an empirical investigation of the way immigration affects labour market outcomes of native born workers in the UK, set beside a theoretical discussion of the underlying economic mechanisms. We discuss the problems that may arise in empirical estimations, and suggest ways to address these problems. Our empirical analysis is based on data from the British Labour Force Survey. We show that the overall skill distribution of Britain's immigrant workforce is remarkably similar to that of the native born workforce. We investigate the impact of immigration on employment, participation, unemployment and wages of the resident population. We find no evidence that immigration has overall effects on any of these outcomes at the aggregate level. There is some evidence that effects are different for different educational groups.
Keywords: 330; Migration; Survey; Attitudes